Visual Performance of Psychological Factors in Interior Design Under the Background of Artificial Intelligence - Xu, Yunkai; Yu, TianTian (Frontiers in Psychology, 2022)
Vision is a kind of sense, and sense is produced by objective things acting on the sense organs. Therefore, the study of sensory process should start from its external stimuli, in order to first understand how it acts on the sensory organs to produce sensory phenomena. This paper mainly studies the visual performance of psychological factors in interior design under the background of artificial intelligence. This paper proposes a K-means clustering algorithm and a localization algorithm fused with visual and inertial navigation. The distance thresholds corresponding to the SIFT feature descriptors of threshold T1, 128D, 96D, 64D and 32D are 170, 160, 150 and 90, respectively. This verifies that the candidate image with the highest number of matching points is considered the best matching image.